Shared liability: The European Parliament's misstep in fighting financial fraud - Matthias Bauer; Andreas Dugo; Dyuti Pandya (European Centre for International Political Economy (ECIPE), 2024)
The rise in financial fraud has prompted regulatory proposals under the Payment Services Regulation in the form of a shared liability model provisioned under Article 59. The potential proposal by the European Parliament could now extend liability beyond Payment Service Providers to Electronic Communications Service Providers and online platforms. While the intent to address fraud is commendable, this model misallocates responsibilities by requiring non-financial entities to oversee fraudulent activities, despite their lack of visibility and technical control over financial transactions. Extending liability to non-financial entities risks undermining consumer vigilance and diluting payment services providers' efforts to maintain fraud awareness. A shared liability regime covering non-financial entities would also disproportionately burden smaller "digital" firms, leading to legal uncertainties, costly legal disputes, and market exits. This would not only drive market concentration and reduce competition in digital services but also undermine EU and Member State efforts to support Europe's lagging digital start-ups and scale-ups. The resulting harm to innovation and entrepreneurship would be a significant setback to the EU's broader digital ambitions.
Keywords: 330